EFEKTIVITAS RPJMDes DALAM PEMBANGUNAN DI DESA HUNTU BARAT KECAMATAN BULANGO SELATAN KABUPATEN BONE BOLANGO - Nur Eng Mokodompit; Iyam Katili (Universitas Muhammadiyah Gorontalo, 2022)
Medium-Term Development Planning is a planning concept that becomes the government's guide in planning national development to villages and sub-districts. As regulated in Law No. 25 of 2004. This study aims to determine the effectiveness of the Medium-Term Village Development Plan in Development in Huntu Barat Village, South Bulango District, Bone Bolango Regency. This type of research is qualitative, with a database based on the results of interviews with informants.The results of the study indicate that the effectiveness of the Mid-Term Development Plan of West Huntu Village in development shows the achievement of the development program in accordance with the vision and mission of the village government. This means that the function of the Village Medium-Term Development Plan is really effective in determining the direction of village development. That it is effective in village development, shows that the stages of the Village Medium-Term Development Plan are implemented in accordance with the provisions and regulations contained in the Village Law Number 6 of 2014 and Law Number 25 of 2004 concerning the national planning system.